Identification of Isonitrile‐Containing Natural Products in Complex Biological Matrices through Ligation with Chlorooximes. Issue 6 (8th December 2022) - Schäfer, Rebecca J. B.; Wilson, Kayla; Biedermann, Maurice; Moore, Bradley S.; Sieber, Simon; Wennemers, Helma
Abstract: Isonitrile‐containing natural products have garnered attention for their manifold bioactivities but are difficult to detect and isolate due to the chemical lability of the isonitrile functional group. Here, we used the isonitrile‐chlorooxime ligation (INC) in a reactivity‐based screening (RBS) protocol for the detection and isolation of alkaloid and terpene isonitriles in the cyanobacterium Fischerella ambigua and a marine sponge of the order Bubarida, respectively. A trifunctional probe bearing a chlorooxime moiety, a UV active aromatic moiety, and a bromine label facilitated the chemoselective reaction with isonitriles, UV‐Vis spectroscopic detection, and mass spectrometric analysis. The INC‐based RBS allowed for the detection, isolation, and structural elucidation of isonitriles in microgram quantities. Abstract : A trifunctional probe consisting of a chlorooxime, a bromine mass tag, and a UV tag facilitated the detection, isolation, and structure elucidation of isonitrile‐containing natural products in microgram quantities in cyanobacteria and a rare marine sponge.